The Mandi Meugang Tradition as a Means of Reinforcing Religious Values in the Kute Cinta Damai Community, Aceh Tenggara - Nurul Hasanah; Juwaini Juwaini; Muhammad Muhammad (Muqaranah Al-Adyan: Multidisciplinary Perspective on Religions, 2025)
The Mandi Meugang tradition is a local cultural practice that continues to be preserved by the people of Kute Cinta Damai, Aceh Tenggara Regency, to this day. This tradition is considered important because it is believed to bring blessings and spiritual purification before the arrival of the holy month of Ramadan. However, over time, the practice of Mandi Meugang has undergone a shift in meaning and implementation due to the community’s declining knowledge of its original procedures and underlying values. This study aims to describe the implementation process of the Mandi Meugang tradition and to explore the religious values embedded within it among the people of Kute Cinta Damai. This research employs a qualitative field study using a phenomenological approach. Data were collected through in-depth interviews with community leaders and tradition practitioners, as well as documentation of ritual activities related to Mandi Meugang. The findings reveal that Mandi Meugang is performed one day before Ramadan, involving several stages such as going to the river, reciting an intention, and bathing using pangir (a mixture of traditional herbs). The tradition embodies several religious values, including self-purification before fasting, gratitude for the coming of Ramadan, the spirit of togetherness, mutual forgiveness, and the strengthening of social bonds among community members. Thus, the Mandi Meugang tradition functions not only as a ritual preparation for Ramadan but also as a medium for preserving religious and communal values within the social life of the Kute Cinta Damai community.